Isolation of human salivary exosome on the morphology and gene expression of human periodontal ligament fibroblast cell line - Tuan Kechik, Tuan Siti Mastazliha Long (2018)
The increasing incidence of periodontal diseases has led to the advancement in periodontal therapy including periodontal tissue regeneration. The development of human salivary-derived exosomes has become one of the promising researches to improve cell-based tissue engineering. Due to established functions showed by exosomes, human salivary exosomes were isolated and its effect on the morphology and gene expression of basic fibroblast growth factor (bFGF) and collagen type 1 (COL1) in human periodontal ligament fibroblast (HPdLF) cell line was studied. Unstimulated saliva samples collected from healthy male subjects were used. Exosomes were isolated by ultracentrifugation while the confirmation and establishment of its storage condition were carried out by Scanning Electron Microscopy (SEM), Western blot assay and Nanoparticle Tracking Analysis (NTA) in the presence and absence of protease inhibitor. Morphology and number of HPdLF cells treated with exosomes were viewed under inverted microscope and calculated by using trypan blue respectively. Determination of the gene expression level of bFGF and COL1 in the presence and absence of human salivary exosomes in HPdLF cells was performed using quantitative reverse transcriptase polymerase chain reaction (RTqPCR). This study showed that salivary exosomes were stable at several temperatures tested with and without protease inhibitor. SEM analysis demonstrated the round shape of exosomes, ranged between 10 nm to 100 nm in diameter. Western blot result confirmed that isolated exosomes expressed exosomal marker CD63. NTA estimated the concentration and individual size of exosomes. There was no significant difference in the morphology and number of HPdLF cells for both exosome treated and untreated samples, however, exosomes upregulated bFGF gene expression. This study concluded that human salivary exosomes are stable biomaterial and able to upregulate bFGF gene that was expressed by HPdLF cells. Thus, they might have potential to be used as alternative biomaterial in tissue engineering for periodontal regeneration.